2018
DOI: 10.1007/978-3-319-58542-0_25-1
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Language Proficiency Tests in Higher Education

Abstract: In higher education, standardized academic language proficiency test scores are often used for multiple purposes, including admissions of international students to degree programs and identification of students' post-entry language support needs. In this chapter, issues surrounding the use of high-stakes standardized academic language proficiency tests for making decisions about international English as-a-second-language (ESL) students are explored. Specifically, a) stakeholders' views and knowledge about stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The findings of the study also extend our understanding of the predictive validity of proficiency scores in academic performance to multilingual speakers who also speak English as a lingua franca, in this case Singaporean students undertaking Englishmedium university education. Furthermore, this finding of our study seemed to echo the argument from the literature of proficiency tests in higher education that locally developed tests could potentially be more representative of students' true competence levels than the internationally standardized proficiency tests, which students might have easily and excessively prepared for on a larger scale (Ockey & Gokturk, 2019). For example, in O'Dwyer et al (2018), even though the predictive validity of TOEFL for GPA was confirmed among a group of undergraduate students in Turkey, the results showed that the correlation between the institution's own proficiency test and the students' GPA (r = .46) was stronger than that between TOEFL and GPA (r = .38).…”
Section: Predictive Effect Of Proficiency Test Scores On Academic Per...supporting
confidence: 75%
See 1 more Smart Citation
“…The findings of the study also extend our understanding of the predictive validity of proficiency scores in academic performance to multilingual speakers who also speak English as a lingua franca, in this case Singaporean students undertaking Englishmedium university education. Furthermore, this finding of our study seemed to echo the argument from the literature of proficiency tests in higher education that locally developed tests could potentially be more representative of students' true competence levels than the internationally standardized proficiency tests, which students might have easily and excessively prepared for on a larger scale (Ockey & Gokturk, 2019). For example, in O'Dwyer et al (2018), even though the predictive validity of TOEFL for GPA was confirmed among a group of undergraduate students in Turkey, the results showed that the correlation between the institution's own proficiency test and the students' GPA (r = .46) was stronger than that between TOEFL and GPA (r = .38).…”
Section: Predictive Effect Of Proficiency Test Scores On Academic Per...supporting
confidence: 75%
“…Competence in language is deemed an essential condition for academic success, therefore universities usually have proficiency requirements for admission of international students, such as test scores from the International English Language Testing System (IELTS) and/or the Test of English as a Foreign Language (TOEFL). As alternatives to IELTS and TOEFL, higher education institutions often accept proof of proficiency through locally developed tests (Cho & Bridgeman, 2012;Coley, 1999;Ockey & Gokturk, 2019). Those alternative proficiency tests are advantageous due to their alignment with local curricula (Green, 2012), and results can provide direct references regarding whether and how to place different students into corresponding levels of proficiency courses after admission.…”
Section: Language Proficiency and Academic Achievementmentioning
confidence: 99%
“…Further, the significant efficacy of the EP programme in relation to students' SGPA in the current study echoed prior research that locally designed EP programmes and tests seemed to be advantageous due to their alignment with the institutional curriculum, and can be potentially more representative of students' true competence than internationally standardised EP tests that might be less representative due to coaching and test preparation effects (Coombe and O'Sullivan, 2012;Ockey and Gokturk, 2019). In the context of Singapore, in particular, it is of great importance for higher education institutions to develop and evaluate their EP programme for both admission and placement decisions, which would better cater to the bi/multilingual speakers speaking English as their first language.…”
Section: Conclusion and Practical Implicationssupporting
confidence: 75%
“…In addition, universities have also been accepting alternative forms of EP evidence such as locally developed language tests (Cho and Bridgeman, 2012;Oliver et al, 2012), which has been described to be beneficial due to their alignment with the local curriculum (Coombe and O'Sullivan, 2012). It was argued that the results of locally developed tests could be more representative of students' true competence levels than those of internationally standardised EP test, considering that students might have intentionally prepared for the internationally standardised tests and hence, could perform above their actual proficiency levels (Ockey and Gokturk, 2019). Moreover, results of locally developed EP tests could serve as direct references about how to assign different students into relevant levels of EP courses in the university after being admitted.…”
Section: Review Of the Efficacy Of Ep Programmesmentioning
confidence: 99%
“…EPT values are used for various purposes, including as a requirement to take part in undergraduate and postgraduate programs at several leading universities in Indonesia, recruitment requirements by many national and multi-national companies in Indonesia, one of the requirements by many companies for employees to be sent for attending seminars, courses or training in English [4]. Besides, EPT can provide important information to stakeholders regarding a person's academic ability [5].…”
Section: A English Proficiency Testmentioning
confidence: 99%